Implementation of Counseling by Unit Kamtibmas for the Prevention of Drug Abuse in Banda Aceh Police Area - Restu Guspriyoga (Indonesian Journal of Police Studies, 2021)
The problem of drug abuse in Indonesia is now very concerning. This is due to several things, among others, because Indonesia is located in a position between three continents and considering the development of science and technology, the influence of globalization, very advanced transportation flows and the shift in materialistic values ​​with the dynamics of targeting opinions on illicit drug trafficking. As for the expected benefits of research on the implementation of counseling by the Bintibmas unit for the prevention of drug abuse in the Banda Aceh Police Legal Area, this research uses a qualitative approach, the qualitative approach was chosen because it is more appropriate in describing and analyzing the problems raised in this study. This type of research is a descriptive analytic approach. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. The sources of data/information in this study consist of primary data sources and secondary data sources. Primary data sources are data obtained directly from the first source, through interviews. Primary data is obtained raw and then analyzed further, this data is presented according to field conditions. While what is meant by secondary data is data obtained through library research by studying literature, scientific writings, laws and regulations and documents obtained from agencies related to the object of writing. The implementation of Bintibmas is carried out in accordance with management theory according to George R. Terry, namely: Planning, Organizing, implementing, and supervising. The results of this study can be seen that the implementation of drug guidance and counseling in the context of drug prevention for students carried out by the Bintibmas Unit of the Banda Aceh Police has implemented management theory.